Effect of Drying Temperature on Physicochemical Qualities and Antioxidant Capacity of Tamarind Shoot and Flower - Srijariya, Khwanchira; Chattong, Utaiwan; Thanaboonrongkom, Sirikarn; Chaikham, Pittaya; Dajanta, Katekan (Burapha Science Journal, 2024)
Background and Objectives : Tamarind leaves are rich in antioxidant polyphenols and bioactive activity. This research aimed to study the effect of drying temperature on the physicochemical qualities, bioactive compounds, and antioxidant effects of tamarind shoot leaves and flowers. Methodology : Drying tamarind shoots and flowers with a hot air drying at 50, 60 and 70oC until water activity (aw) values were lower than 0.5. Physicochemical qualities including aw, brightness (L*), redness (a*) and yellowness (b*) values of dried tamarind shoots and flowers were examined. In addition, antioxidant properties including total phenolic compounds, total flavonoids, 2,2-diphenyl-1-picrylhydrazyl (DPPH)-radical scavenging activity and ferric reducing antioxidant power (FRAP) of the hot water extracts of dried tamarind shoots and flowers were evaluated. Main Results : The values of water activity of dried samples were ranged 0.35 – 0.43. The L* and b* values of dried tamarind shoot leaves were significantly increased when drying temperature rose (P≤0.05). The extract of tamarind shoots dried at 50ºC for 3.5 h exhibited the highest values of total phenolic compounds (3.10 mg GAE/g), flavonoids (1.54 mg CE/g) and FRAP value (6.64 mg TE/g). Moreover, the extract of tamarind shoot leaves found to have significant greater potent of antioxidant capacity than those found in flower part (P≤0.05). Conclusions : Tamarind shoot leaves exhibited higher antioxidant quality than those found in the flower part. The optimal drying condition for tamarind shoot leaves was 50oC for 3.50 h resulting in the superior antioxidant quality than those found in other drying temperature.